The Oligo-Miocene siliciclastic foreland basin deposits of northern Tunisia:Stratigraphy, sedimentology and paleogeography. (October 2020) - Boukhalfa, Kamel; Soussi, Mohamed; Ozcan, Ercan; Banerjee, Santanu; Tounekti, Abdelbasset
Abstract: This paper presents an integrated study aiming to assess the stratigraphy, sedimentology and paleogeography of the marine and non-marine Tellian, Bejaoua and Fortuna Oligo-Miocene deposits of northern Tunisia. The fossiliferous strata, particularly the glauconite-rich facies, bounded by major unconformities, refine the stratigraphic framework and address the spatio-temporal relationship between marine and non-marine deposits. Three new updated paleogeographic maps for the Oligocene (30-27 Ma) and the Miocene (21-20 Ma and 15 Ma) epochs, outlining the major transgressive and regressive events and the relationships between the Tellian and Atlasic basins have been produced. The genesis and evolution of the Oligo-Miocene foreland sub-basins of the Tellian, the salt domes zone and the northern Atlas are reconstructed considering the geodynamic events that accompanied the African-Eurasian convergence, besides eustasy and climate. Highlights: The Oligo-Miocene siliciclastic succession of northern Tunisia has been revised based on ancient and new acquired biostratigraphic data. New lithostratigraphic scheme outlines the spatio-temporal distribution of the continental and marine facies of the Tellian and Atlasic domains. Transgressive events versus glauconitic events.